The impact of gender difference on clinical and echocardiographic outcomes in patients with heart failure after cardiac resynchronization therapy: A systematic review and meta-analysis. - Fa-Hui Yin; Chun-Lei Fan; Ya-Ya Guo; Hai Zhu; Zhi-Lu Wang (PLoS ONE)
Background Cardiac resynchronization therapy(CRT) has been recommended as a standard treatment for patients with advanced heart failure. However, some studies have reported different clinical and echocardiographic outcomes between male and female patients who received CRT. This Meta-analysis is to determine whether gender difference has any significant impact on clinical and echocardiographic outcomes in patients with heart failure after CRT. Methods and results PubMed, Embase, and the Cochrane library database were searched. A total of 149,259 patients in 11 studies were identified. Our analysis demonstrated that women showed lower all-cause mortality than men after CRT (odds ratio[OR] 0.50, 95% confidence interval [CI] 0.36 to 0.70). No significant difference was observed in the increment of New York Heart Association (NYHA) functional class(standard mean difference[SMD] -0.07,95% CI -0.15 to 0.01), 6-minitue walk distance (6-MWD) (SMD -0.05, 95% CI -0.07 to 0.17), and quality of life (QoL) (SMD -0.10, 95% CI -0.23 to 0.03). With respect to the echocardiographic parameters, women exhibited statistically significant improvement in left ventricular ejection fraction (LVEF) (SMD 0.25,95% CI 0.07 to 0.43), and decrement of left ventricular end diastolic diameter (LVEDD) (SMD -0.27, 95% CI -0.39 to -0.25) as compared with men. No significant difference was observed in left ventricular end diastolic volume (LVEDV) (SMD -0.08, 95% CI -0.28 to 0.08) and left ventricular end systolic volume (LVESV) (SMD -0.16, 95% CI -0.40 to 0.09) between men and women. Conclusion Women seem to obtain greater benefits from CRT both in clinical and echocardiographic outcomes compared with men. But as this gender superiority could be observed only during long-term follow-up periods, further studies are needed to elucidate exact reasons for this phenomenon.